PENGARUH PEGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAAWAN PERKEBUNAN PTPN V (Studi Bagian Produksi CPO Unit Terantam Kampar) - Yanti, Evi; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is motivated by the importance of human resources in a company to be able to produce quality products amid business competition in the era of globalization. Human resources are an important role for the success of the PTPN V Unit Terantam Kampar Palm Oil Mill, because humans are living assets that need to be maintained and developed. To increase work productivity, company employees must pay attention to what factors serve as a support in influencing employee performance. This research was conducted at PTPN V Unit Terantam Kampar Palm Oil Mill. The purpose of this study was to determine the level of performance of employees in the production department at the PTPN V Unit Terantam Kampar Palm Oil Mill. The research sample was taken as many as 63 respondents using the sampling method. In this research, the methods used are descriptive and quantitative. The data obtained from the results of interviews and questionnaires / questionnaires were then tested with statistics through the SPSS program. The method of analysis used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that supervision has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, and supervision and work discipline have a positive and significant effect on employee performance at the PTPN V Palm Oil Mill Unit Terantam Kampar. Keywords: Supervision, Work Discipline, Employee Performance